Developing Childrens's Fine Motors Through Used Materials to be Useful Tools in Early Childhood - Saraswati, Inayah Karsa (Early Childhood Research Journal (ECRJ), 2021)
Fine motor skills are one aspect of development that must be developed in early childhood. This aspect relates to physical movements that involve small muscles, such as coordination between the eyes and hands in carrying out several activities, such as grasping, drawing, sticking, shaping and tracing. Objective:: To examine literature, journals and research documents that identify through used materials which are useful tools in developing fine motor skills at an early age. Method: Search for research journals using specific words in the period 2015-2020. There were 65 research journals on fine motor skills and the use of used goods as useful tools both nationally and internationally, 27 journals met the criteria, 38 journals did not meet the criteria, only 20 selected journals met the criteria. 15 national journals and 5 international journals. Results and discussion: Literature review shows that using used materials as a useful tool can significantly help develop fine motor skills in early childhood. Statistical analysis proves that this method can increase the knowledge and actions of parents, teachers, and the community in using used goods as useful tools. Conclusion: Using used goods can significantly develop children's fine motor skills by making it a useful tool.